The use of modified keystone flap in periarticular or large superficial tumor resection surgery. Issue 7 (3rd March 2020) - Fang, Shuo; Li, Yingli; Tang, Weiya; Zhu, Weiye; Zhuang, Wei; Xing, Xin; Yang, Chao
Abstract: Background and Objectives: The keystone design perforator island flap (KDPIF) is often used to cover defects in reliable blood supply and similar skin patterns, but its mobility is limited, especially when the wound is large or occurs around joints. Here, we describe a modified KDPIF, boat‐shaped flap. We added a V shape along the lateral arc, forming a V‐Y flap on KDPIF's outer arc shapes like a sail. This paper also describes a clinical study to evaluate this method. Method: From September 2014 to March 2017, 31 patients were operated on using the boat‐shaped flap in our department and were followed up annually with clinical evaluation. The wound locations included joints (n = 11), trunk (n = 18), and face (n = 2). Fifteen defects were ≥5 × 5 cm 2 . Results: After 6 to 24 months of follow‐up, 29 patients had first‐intention healing and were satisfied with the morphology and function. Secondary healing was observed in two patients, and the wounds were closed after dressing treatment for 2 weeks. Conclusion: The boat‐shaped flap enhances the mobility and achieves strong resistance to tension. The modified curvilinear shape prevents the joint activity from being restricted, with visually concealed scars. It is particularly applicable for repairing large wounds and defects around joints.